Clinical experience of thyroid carcinoma: a study of 178 cases - Ece, Harman; Devrim, Cetinkaya Dölek; Pelin, Tutuncuoglu A.; Ahmet, Gorgel; Ozgur, NIflIoglu M.; Mustafa, Harman; Mithat, Bahceci (Contemporary Oncology/Współczesna Onkologia, 2012)
Aim of the study : Thyroid carcinoma is the most common malignancy of endocrine organs. The prognosis varies. Factors such as age, sex, size of the tumor, stage of disease, presence of extrathyroidal spread, and completeness of resection have been found to significantly influence prognosis. We aimed to evaluate clinical features of our patients with thyroid carcinoma, prospectively. Material and methods: We evaluated total 178 patients treated between 2010 and 2011 at the Department of Endocrinology, I.zmir Atatürk Training Hospital, retrospectively. Data on patients, tumors, and therapeutic approaches were collected. All results are shown as mean ± standard deviation (SD). P values were based on two-sided tests with a cutoff for statistical significance of 0.05 and 95% confidence interval. Results: There were no differences between female and male patients according to histopathological subtypes, demographic data and prognostic findings of thyroid cancer. The assessment of tumor size and other prognostic factors revealed that there was a correlation between tumor size and capsular and/or vascular invasion. In the postoperative evaluation we detected a correlation between metastases and vascular invasion and/or capsular invasion but there was no significant relation between focus (solitary/multifocal) and metastases. Conclusion: There was no significant difference in terms of gender and age (< 45 years of age and ≥ 45 years of age) among the patient groups (low risk/intermediate risk/high risk). By multiple regression analysis among metastasis and prognostic factors it was observed that vascular invasion and thyroglobulin levels affect development of metastases.